1 - Introduction: Public Sector Reforms and the Quest for Democratic Developmentalism in Africa - Edigheji, Omano (Africa Development, 2021)
Developmentalism has been one of the main justifications for public sector reforms. In what concerns Africa, this, in part, has been based on the assumption that public sector reforms, which will make the state effective, efficient, responsive, accountable and productive, are necessary conditions for the development of the continent. Not surprisingly, a plethora of public sector reforms has been initiated and implemented. The intersection, synergies, complementarities and, at times, disjunctures between the reforms and the continent’s quest for devel- opment, may not have received the scholarly attention it deserved, beside a few exceptions, including the work of the late Professor Guy Mhone. Therefore, this introductory article will focus on the public sector reforms in Africa, especially as from the 1980s, and will necessarily draw heavily on the work of Guy Mhone.